Recent Advances and Perspectives in Single-Ion COF-Based Solid Electrolytes - Hong Zhao; Xiangkun Bo; Xiucai Wang; Yaqi Ren; Zhaohuan Wei; Walid A. Daoud (Batteries, 2023)
The rapid growth of renewable energy sources and the expanding market for electric vehicles (EVs) have escalated the demand for safe lithium-ion batteries (LIBs) with excellent performance. But the limitations of safety issues and energy density for LIBs continue to be obstacles to their future use. Recently, single-ion covalent-organic-framework-based (COF-based) solid electrolytes have emerged as a promising avenue to address the limitations of traditional liquid electrolytes and enhance the performance of LIBs. COFs have a porous structure and abundant electron-donating groups, enabling the construction of an available ionic conductive network. So, COFs are the subject of extensive and in-depth investigation, especially in terms of the impacts their adjustable porous structure and tunable chemistry on the research of ionic transport thermodynamics and transport kinetics. In this perspective, we present a comprehensive and significant overview of the recent development progress of single-ion COF-based solid electrolytes, highlighting their rare performance and potential applications in solid lithium batteries. This review illustrates the merits of single-ion conducting solid electrolytes and single-ion COF conductor-based solid electrolytes. Furthermore, the properties of anionic, cationic, and hybrid single-ion COF-based conducting electrolytes are discussed, and their electrochemical performance is also compared when applied in Li-ion batteries. Finally, to solve challenges in COF-based Li-ion batteries, strategies are provided to obtain a high lifespan, rate performance, and stable and safe batteries. This work is promising to offer valuable insights for researchers and the energy storage industry.